1999
DOI: 10.1200/jco.1999.17.9.2896
|View full text |Cite
|
Sign up to set email alerts
|

Number of Nodes Examined and Staging Accuracy in Colorectal Carcinoma

Abstract: In a sample of patients statistically similar to the sample in the NCDB report, the examination of at least 14 nodes after resection of T2 or T3 carcinoma of the colon and rectum will accurately stage the lymphatic basin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
209
1
18

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 314 publications
(232 citation statements)
references
References 14 publications
4
209
1
18
Order By: Relevance
“…It has been shown that the total number of lymph nodes recovered and examined has an impact on the accurate staging of colorectal carcinoma. 9,10 The explanation for this finding is that failure to resect and analyze a sufficient number of lymph nodes may result in inadvertently missing small but clinically important metastatic deposits. These same studies indicate that at least 14 lymph nodes per specimen must be examined for staging to be accurate.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the total number of lymph nodes recovered and examined has an impact on the accurate staging of colorectal carcinoma. 9,10 The explanation for this finding is that failure to resect and analyze a sufficient number of lymph nodes may result in inadvertently missing small but clinically important metastatic deposits. These same studies indicate that at least 14 lymph nodes per specimen must be examined for staging to be accurate.…”
Section: Discussionmentioning
confidence: 99%
“…There is a controversy, however, in the literature about whether the number of lymph nodes resected and evaluated impacts patient outcomes [29,30]. Further ambiguity exists even among the proponents of this quality metric regarding the exact number of lymph nodes needed to accurately stage a patient with colon cancer [5,[7][8][9][10][11][12][13][14][15][16][17][18]. Still, in the absence of a unique molecular signature of a colon tumor that dictates therapies and predicts a patient's course, the American College of Surgeons, ASCO, NCCN and others have adopted this as an indicator for quality assessment [24,26].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%
“…There has been great discussion and variability in the literature about the number of nodes that need to be examined to stage patients with accuracy [5,[7][8][9][10][11][12][13]. In addition, a substantial body of literature suggests that the absolute number of lymph nodes removed, whether positive or negative, is independently correlated with survival [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A higher number of LN retrieved in the surgical specimen increases the probability of metastatic LN; therefore, patients with stage III rectal cancer might have a higher average number of LN examined than do stage I-II patients [28,39]. In our study, we observed that the median number of LN harvested was lower in stage I-II patients than in stage III patients (p = 0.079).…”
Section: Discussionmentioning
confidence: 47%
“…. Nevertheless, the number of metastatic LN is related not only to the depth of tumor wall invasion, but also on the number of LN examined [26][27][28], which, in turn, varies depending on several other factors, including patient-related variables (age, gender, body mass index), tumorrelated variables (size, stage, and grade), the surgeon, and the pathologist [29].…”
Section: Discussionmentioning
confidence: 99%